IQOMIC: Qoute and Comic Persuasive Da'wah on Gen Z in Social Media - Aswar Tahir; Nabilah El Rofidah; Selvira Diva Ardhinda; Faizatul Mukarromah (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2025)
In the current era of communication and information which is marked by the rise of mass media as a means of mass communication and a means of forming public opinion, missionaries and da'wah activists have used the mass media as a means of preaching. Dakwah is not only carried out verbally, but can be done through written media such as books, novels, short stories, and comics. Comics have now developed as a popular media in constructing discourse or public opinion that can describe people's lives. Although many media have sprung up to express criticism and information, the appeal of comics is not inferior to other media. The packaging of stories and communication messages that are funny, interesting, and light makes comics very popular. Da'wah messages are conveyed through narration, dialogue, and pictures contained in comics. Comics as a medium of da'wah are able to reach a wider audience, especially the younger generation who tend to be more interested in visual media. Da'wah messages also show that the use of persuasive techniques in comics can strengthen the preaching messages conveyed. Persuasive techniques such as using authority figures, using humor, and using emotions can influence readers to adopt Islamic values conveyed in comics. Comics as a medium of da'wah can be an effective alternative for conveying persuasive da'wah messages to the public, especially the younger generation. Da'wah messages can be conveyed through various themes and effective persuasive techniques. Become a reference material for comic creators and da'wah content creators to create content that is effective in conveying persuasive da'wah messages.